Factors affecting on renting decision of residential property in Titiwangsa, Kuala Lumpur - Mohd Zaini, Al Zaim (2024)
In this research study, the factors affecting renting decision of residential property in Titiwangsa, Kuala Lumpur has been identified. The purpose of this research study has been conducted mainly to get an overview and result regarding the factors affecting renting decision of residential property renters. Generally, knows that a house is essential to humans as provides shelter, safety and comfort However, the ability to buy a house in urban areas like Kuala Lumpur is quite hard due to rising property prices and living cost. The research study has been well conducted with the target respondent who has rented a residential property in Titiwangsa, Kuala Lumpur. There are two objectives that need to be achieved throughout this study which are to identify the factors influencing on renting decision of residential property in Titiwangsa, Kuala Lumpur and to analyse the most important factors of renting decision in residential property in Titiwangsa, Kuala Lumpur. From the previous journals, 7 factors were found which are housing loan, financial considerations, housing price, neighborhood and public amenities, affordable housing, household income and flexibility to move which can be applied to achieve the first objective which is to identify the factors influencing renting decision of residential property in Titiwangsa, Kuala Lumpur. For the next objective, a total of 235 respondents involved in this research study and the questionnaire form has been distributed among them. This research study used the reliability analysis which is pilot study in addition with descriptive analysis in order to analyse the data. Based on the findings, the factors that showed to be the most important are the housing price. From the analysis, the housing price are the main factor in renters’ preference in Titiwangsa, Kuala Lumpur due to rapidly growing housing prices in Kuala Lumpur and the rising property prices relative to income.